Evaluasi Niat Penggunaan Sistem Informasi Dosen (SIADO) Oleh Dosen Universitas Brawijaya Dengan Menggunakan Technology Acceptance Model (TAM) Termodifikasi - Larizza Novianti; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the implementation of SIADO UB there are obstacles related to the lecturer's intentions to use it as users. An evaluation of the intention of SIADO usage by UB lecturers is required to produce recommendations to improve the utilization of SIADO UB. This study will evaluate five variables based on Technology Acceptance Model (TAM) that has been modified, ie perceived usefulness, perceived ease of use, trust, social influence, facilitating conditions, and usage intention variables. This research used quantitative method with the instrument of questionnaire and sample data which was chosen freely. The population of this research is 2192 active lecturers in Universitas Brawijaya. To determine the number of samples in this study using slovin formula equation with a degree of leeway of 10% and obtained the sample of 96 lecturers from all faculties in Universitas Brawijaya. The results showed that the variables perceived usefulness (71.0%), perceived ease of use (73.3%), social influence (66.2%), facilitating conditions (72.3%), and trust (73.8%) included in the high category and the usage intention (75.2%) variables included in very high categories. Recommendations from the results of this research are such as through security efforts on SIADO UB, increase the speed of system's responses, the layout of the display is more easy to understand and as needed, and ease to be accessed anywhere and anytime